2018
DOI: 10.1080/14756366.2018.1474212
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and in vivo anti-ulcer evaluation of some novel piperidine linked dihydropyrimidinone derivatives

Abstract: Dihydropyrimidinone derivatives containing piperidine moiety were synthesised in a good yield. All the compounds were confirmed by elemental analysis and spectral data. Anti-ulcer activity of novel dihydropyrimidinone-piperidine hybrids (1–18) was evaluated. Among them, four compounds (3, 8, 11 and 15) were found to be most active in 80% ethanol-induced ulcer experimental animal model. All the potent compounds were further evaluated for anti-ulcer activity by different in vivo anti-ulcer models to study the ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…The eight protons of morpholine moiety were observed as triplets at δH 3.20–3.22 ppm with coupling constant ( J = 4.7 Hz) for four protons and another triplet at δH 3.72–3.82 with coupling constant ( J = 4.6 Hz) for four protons. The H-4 and =CH protons of dihydropyrimidinone moiety were observed at δH 5.32–6.08 and 7.79–8.24 ppm, respectively [ 37 , 38 , 39 ]. 13 C NMR spectra confirmed the presence of all carbon atoms of compounds ( 1 – 20 ).…”
Section: Resultsmentioning
confidence: 99%
“…The eight protons of morpholine moiety were observed as triplets at δH 3.20–3.22 ppm with coupling constant ( J = 4.7 Hz) for four protons and another triplet at δH 3.72–3.82 with coupling constant ( J = 4.6 Hz) for four protons. The H-4 and =CH protons of dihydropyrimidinone moiety were observed at δH 5.32–6.08 and 7.79–8.24 ppm, respectively [ 37 , 38 , 39 ]. 13 C NMR spectra confirmed the presence of all carbon atoms of compounds ( 1 – 20 ).…”
Section: Resultsmentioning
confidence: 99%
“…For compounds containing the piperidine ring system in their chemical structure, many pharmacological activities such as antibacterial, antifungal, anticancer, antioxidant, antiulcer, and renin inhibitor have been reported [18][19][20][21][22][23][24]. In addition, the electrochemical properties of many groups of compounds containing piperidine rings have been examined and it has been reported that they show very different electrochemical properties [25][26][27].…”
Section: Introductionmentioning
confidence: 99%